(untitled) (Global Business Management Review (GBMR), 2022)
Present study examined the psychometric properties of the multiple leadership questionnaires (MLQ) in the health sector of Pakistan. Three hundred and fifteen medical doctors participated in the survey from all four regions of Sindh province. Using Smart-PLS 2.0 M3 software the data was analyzed. The results of the present study revealed that all the leadership styles including transformation, transactional and laissez-faire were highly relevant. The results of the study also demonstrated adequate level of internal consistency reliability, convergent validity and discriminant validity for each of the leadership styles. Based on the results, it is suggested that the MLQ instrument could be useful for measuring all the leadership styles in the health sector in Pakistan.